Sovereign Risk Dynamics in the EU: The Time Varying Relevance of Fiscal and External (Im)balances - António Afonso; José Alves; Sofia Monteiro (Center for Economic Studies and ifo Institute (CESifo), 2024)
Acknowledging the potential detrimental impact that twin-deficits may have on sovereign risk, this study uses a two-step approach to assess the impact of fiscal and external sustainability on sovereign risk dynamics for a panel of 27 European Economies between 2001Q4 and 2022Q3. To do so, we first estimate a country-specific time-varying measure of fiscal sustainability, through the cointegration between government revenues and expenditures, and of external sustainability, derived from the exports-imports cointegration. We then resort to those time-varying coefficients to assess their impact on sovereign risk, proxied by 10-year CDS and CDS spreads (against the US) making use of Weighted Least Squares (WLS) analysis. Noticeably, we show that an improvement of both fiscal and external sustainability lead to a reduction in sovereign risk. This phenomenon becomes notably pronounced, particularly when examining countries experiencing an upward trajectory in their public debt levels.
Keywords: C23; F45; G23; G32; H63; 330; sovereign risk; fiscal sustainability; external sustainability; CDS; CDS spreads